E-LEARNING, SOCIAL SUPPORT, AND ACADEMIC STRESS ON PERCEIVED PROBABILITY OF ON-TIME GRADUATION: SELF-EFFICACY AMONG GRADUATE STUDENTS - Lilik Khomsatin Romadhoni; I Putu Putra Astawa; Mirah Ayu Putri Trarintya (Universitas Labuhanbatu, 2026)
Purpose – This study aims to examine the influence of e-learning, social support, and academic stress on perceived probability of on-time graduation through self-efficacy among master's degree students at public universities in Bali.Methodology – This research employed a quantitative explanatory approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). The population consisted of active master's students enrolled at Universitas Udayana, Universitas Pendidikan Ganesha, and Universitas Hindu Negeri I Gusti Bagus Sugriwa. A total of 365 respondents were selected using proportional random sampling. Data were collected through structured questionnaires and analyzed using SmartPLS 4 software.Findings – The results indicate that e-learning and social support have positive and significant effects on self-efficacy and the perceived probability of on-time graduation. Conversely, academic stress negatively affects both self-efficacy and perceived probability of on-time graduation. Self-efficacy significantly influences students’ perceptions regarding their likelihood of graduating on time and partially mediates the relationships between e-learning, social support, academic stress, and perceived probability of on-time graduation. The model explains 50.3% of the variance in self-efficacy and 38.6% of the variance in perceived probability of on-time graduation.Contributin – This study contributes to the literature on educational psychology and higher education management by integrating technological, social, and psychological factors into a comprehensive model explaining graduate students’ perceptions of timely graduation. The findings have practical implications for universities seeking to develop effective academic support systems, strengthen social support networks, and reduce academic stress, thereby improving students’ confidence and academic success.